THE LEGAL FRAMEWORK OF INSOLVENCY IN UZBEKISTAN - Yakhshiboev Mirvokhid Gulboy ugli (Scholar Express Journals, 2025)
The article examines the legal framework of insolvency in Uzbekistan, focusing on both theoretical aspects and practical application. It analyzes the current legislation governing insolvency proceedings, including the Bankruptcy Law, which is the new regulatory act “On Insolvency” and recent reforms aimed at improving efficiency and creditor protection. Special attention is paid to the judicial procedure for the consideration of cases, mechanisms for monitoring the actions of debtors and creditors, as well as government support measures aimed at stabilizing the financial system. The main aspects of legal regulation that contribute to reducing the risk of abuse and ensuring transparency of procedures have been identified, which is an important element in maintaining the trust of market participants.
Keywords: Insolvency; bankruptcy; Uzbekistan